2019
DOI: 10.1017/s1366728918001232
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology finds no inherent delay for grammatical gender retrieval in non-native production

Abstract: Late second language (L2) learners experience pervasive difficulty mastering grammatical gender, and a comprehensive account of this deficit has yet to emerge. We investigate a previously unexamined aspect of L2 gender use: the time course of lexical feature retrieval. Using event-related potentials (ERPs) with a covert production task, we examined whether L2 gender retrieval is delayed relative to phonology and to the time course of feature retrieval in native speakers for familiar nouns whose gender particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Although previous studies with learners of L1 and L2 that both have agreement were not found to show this structural contrast in attraction effects (e.g., Spanish–English bilinguals; Tanner, 2011), it is questionable whether other structural manipulations that potentially change the relative activation levels of the subject and attractor noun influence the degree to which non-native speakers become susceptible to interference. It is also reasonable to expect that the pattern of findings in the present study extends to other cases where L2-specific computations are required, such as English–Spanish bilinguals’ use of the gender cue when checking Spanish gender agreement (e.g., Shantz & Tanner, 2019). These questions remain to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 75%
“…Although previous studies with learners of L1 and L2 that both have agreement were not found to show this structural contrast in attraction effects (e.g., Spanish–English bilinguals; Tanner, 2011), it is questionable whether other structural manipulations that potentially change the relative activation levels of the subject and attractor noun influence the degree to which non-native speakers become susceptible to interference. It is also reasonable to expect that the pattern of findings in the present study extends to other cases where L2-specific computations are required, such as English–Spanish bilinguals’ use of the gender cue when checking Spanish gender agreement (e.g., Shantz & Tanner, 2019). These questions remain to be investigated in future studies.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Guo & Peng (2007) showed that, in L2 production, semantic features are retrieved earlier than phonological features. Shantz & Tanner (2020) found that L2 speakers, not differently than L1 speakers, can retrieve grammatical gender and phonological features in a non-ordered fashion, depending on the type of task. Although limited to L1 speakers, there is also evidence that the retrieval of phonological features can occur concurrently with the retrieval of semantic features (Abdel Rahman & Sommer, 2003).…”
Section: Feature Availability and Sentence Processingmentioning
confidence: 86%
“…For example, studies have shown that, in speech production, the access of semantic and phonological information is not strictly ordered (with phonological information coming after semantic information) and both sources of information may even be consulted in parallel (Abdel Abdel Rahman & Sommer, 2003;Guo & Peng, 2007). Two studies have also shown equally unordered and task-dependent access for morphological and phonological information for L1 (Shantz & Tanner, 2017) and L2 speakers (Shantz & Tanner, 2020).…”
Section: A Processing Compatible Grammarmentioning
confidence: 99%